Pengaruh Siklus Hidup Perusahaan Dalam Memoderasi Hubungan Manajemen Laba Dan Cost Of Equity Capital - Indri Adelina Rizal; Nurzi Sebrina (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to provide empirical evidence whether earnings management can influence the cost of equity capital and whether the company's life cycle can strengthen or weaken the relationship between earnings management and the cost of equity capital. Profit Management in this study was measured using a discretionary accrual proxy. The company's life cycle is measured using the company's cash flow pattern and the cost of equity capital measured using measurements from Ohlson's (1995) model modified by Utami (2005). This study is classified as causative research. The population in this study are manufacturing companies listed on the Indonesian Stock Exchange period of 2013 to 2017.By using purposive sampling method, there were 60 companies as the research’s sample. The type of data used is secondary data obtained from www.idx.co.id. The analysis used in this study is multiple linear regression analysis. The results of this study are that earnings management has no significant positive effect on the cost of equity capital and the company's life cycle is not able to strengthen or weaken the relationship of earnings management with the cost of equity capital.